Exploring the students - Vina Kurnia Dewi; Putu Dian Danayanti Degeng; Khairil Azwar Razali (Journal on English as a Foreign Language, 2024)
Numerous scholarly investigations have been conducted on students' perceptions of integrating information and communication technology (ICT) in English language teaching (ELT). However, existing research lacks specific exploration of students' perceptions regarding web-based and non-web-based ICT in vocational high schools across perspectives of understanding, ease of learning, and learning challenges. Therefore, this study aims to investigate students' perceptions of ICT integration in ELT, specifically examining web-based and non-web-based ICT across perspectives of understanding, ease of learning, and learning challenges. The research method used was a case study. The research involved six students of the two departments (Engineering and Management) at a vocational high school in Malang, Indonesia, as the participants. Data were collected through interviews and analyzed thematically. Results indicate that, based on perspectives of understanding and ease of learning, students exhibit positive attitudes towards integrating ICT, particularly web-based tools like Canva, Quizizz, and Wordwall, alongside non-web-based tools such as LCD and tablet, citing enhanced learning processes. Conversely, in the perspective of learning challenges, challenges like poor internet connectivity for web-based ICT and operational issues for non-web-based tools persist. This study emphasizes the importance of a balanced approach to ICT integration to meet diverse learning needs.